A mobile application developed for scaffolding ESL learners in providing peer feedback. - Catherine, Nguoi Chui Lam (Penerbit Universiti Sultan Zainal Abidin, 2022)
Background and Purpose: Peer feedback has received significant research attention in teaching and learning of oral presentation skills. However, literature reveals a number of challenges concerning students’ provision of peer feedback. A mobile application was thus developed to scaffold students in this context. This study purports to evaluate the efficacy of the developed application by introducing it to the target users in an actual classroom setting. Methodology: Thirty-three (33) ESL learners from one of the polytechnics in Malaysia were involved in this descriptive study. Both the peer feedback records (pre- and post-) were analyzed for the differences in peer feedback before and after the implementation of mobile application. A 20-item questionnaire was later administered to the target group to examine their perceptions on the developed application. Findings: It was revealed that with the use of the newly developed application, students generally constructed more peer feedback with specific suggestions to improve oral presentation. Positive perceptions regarding the presentation, visual design, navigation and mobile app accessibility were also found. Contributions: This study adds to the limited research on the use of mobile-assisted peer feedback, which can be a practical way to develop ESL learners’ oral presentation skills. The findings offer insights into how a mobile application can help scaffold students in peer feedback provision and could help inform that scaffolding is deemed necessary in building an effective classroom culture of feedback. The outcome could serve as a guide for instructors who wish to contemplate using similar approach.